Novel Gadis Pantai Karya Pramoedya Ananta Toer - Dara Windiyarti (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2017)
The purpose of this study was to describe the objectification of women in the Gadis Pantai novel work Pramoedya Ananta Toer, published in 2007. The theory used in this research is feminist about gender differences. The data collection was done by using literature. The method used to analyze data is descriptive analysis.This discussion resulted in the following points. First, the social stratification of society that social class of the nobility (flag) and grassroots groups (the majority), creates the relation between women as objects and men as subjects. Second, the weak role of women in society and the family, facilitate the ongoing objectification of women. Third, the objectification of women has always led to the violence that makes women find it difficult to rise.. Keywords: gender, women, objectification